Biomechanical behaviour of PEDOT:PSS-based hydrogels as an electrode for stent integrated enzyme biofuel cells. Issue 3 (March 2022) - Antipova, Christina G.; Parunova, Yulia M.; Vishnevskaya, Maria V.; Krasheninnikov, Sergey V.; Lukanina, Ksenia I.; Grigoriev, Timofei E.; Chvalun, Sergei N.; Gotovtsev, Pavel M.
Abstract: The possibility of creating a biofuel cell based on a metal stent was shown in this study. Given the existing stent implantation approaches, the integration of a biofuel cell into a stent naturally entails capacity for biofuel cells to be installed into a human body. As a counter electrode, a hydrogel based on iota-carrageenan, polyvinyl alcohol, and PEDOT:PSS, with an immobilized glucose oxidase enzyme, was proposed. Tension tests demonstrated that the hydrogel mechanical behavior resembles that of a bovine's vein. To obtain an analytical description, the deformation curves were fitted using Gent and Ogden models, prompting the fitting parameters which can be useful in further investigations. During cyclic biaxial studies the samples strength was shown to decreases insignificantly in the first 50 cycles and, further, remains stable up to more than 100 cycles. The biofuel cell was designed with the PEDOT:PSS based material as an anode and a Co–Cr self-expanding stent as a cathode. The maximum biofuel cell power density with a glucose concentration of 5 mM was 7.87 × 10 −5 W in phosphate buffer and 3.98 × 10 −5 W in blood mimicking buffer. Thus, the biofuel cell integration in the self-expanding stent was demonstrated. Abstract : Biosensors; PEDOT:PSS; Biotechnology; Internet of things; Biofuel cell.